2009
DOI: 10.4103/0378-6323.45221
|View full text |Cite
|
Sign up to set email alerts
|

The rK39 immunochromatic dipstick testing: A study for K39 seroprevalence in dogs and human leishmaniasis patients for possible animal reservoir of cutaneous and visceral leishmaniasis in endemic focus of Satluj river valley of Himachal Pradesh (India)

Abstract: The positive rapid rK39 immunochromatographic dipstick test in 100% VL and 31.8% LCL patients, and 6.5% dogs suggests that both VL and LCL in this focus are apparently being caused by L. donovani-infantum and that reservoir infection is perhaps being chiefly maintained in asymptomatic dogs. However, it needs corroborative evidence in the form of in-vitro parasite cultivation and/or PCR studies for confirmation. A more elaborate study is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
8
22
0
Order By: Relevance
“…11 In Himachal Pradesh, India, anti-Leishmania antibodies were detected in two of 31 dogs using the rK39 immunochromatographic test (ICT). 12 Furthermore, Phlebotomus argentipes, the only known vector for L. donovani in the Indian subcontinent, is zoophilic, which supports the hypothesis of a zoonotic L. donovani transmission cycle.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…11 In Himachal Pradesh, India, anti-Leishmania antibodies were detected in two of 31 dogs using the rK39 immunochromatographic test (ICT). 12 Furthermore, Phlebotomus argentipes, the only known vector for L. donovani in the Indian subcontinent, is zoophilic, which supports the hypothesis of a zoonotic L. donovani transmission cycle.…”
Section: Introductionsupporting
confidence: 55%
“…26 Our observations of anti-Leishmania antibodies and Leishmania DNA in blood samples obtained from stray dogs corroborate the findings of previous studies in Sri Lanka, 10 Sudan, 2 and India. 12 In Bangladesh, cattle that are seropositive for leishmaniasis have been found, but there is no evidence of Leishmania DNA, 13 suggesting that cattle do not play a role as reservoir hosts. In a recent study, Leishmania DNA was detected in a single (1.2%) dog among 85 stray dogs using DNA extracted from whole blood spotted on filter paper.…”
Section: Discussionmentioning
confidence: 99%
“…Leishmania DNA was detected in one sample taken from a stray dog in Fulbaria upazila using ITS1-PCR approach, as described previously [18], and sequencing analysis of the rRNA-ITS region and cytochrome b gene confirmed that this stray dog was infected with the L. donovani parasite. The presence of L. donovani DNA in the blood sample from a stray dog in our study supports the findings of a previous study in Sri Lanka [16], Sudan [11], and India [19]. In a more recent study in Nepal, Leishmania DNA was found in several domestic animals such as goats, cows and buffaloes from an endemic area several months after the active transmission season [4], but there was no evidence of Leishmania DNA in domestic cattle in Bangladesh, although the cattle were seropositive for leishmaniasis [1].…”
supporting
confidence: 82%
“…Recently, Leishmania amastigotes from skin exudates of dogs in Sri Lanka [16], and Leishmania DNA from several domestic animals, including goats, cows and buffaloes, was detected in Nepal [4]. In Himachal Pradesh, India, two dogs out of 31 were positive for anti-Leishmania antibodies using a rK39 immunochromatographic rapid test [19]. These findings strengthen the idea of an animal reservoir for L. donovani in Bangladesh.…”
supporting
confidence: 64%
“…In the Indian subcontinent and East Africa, anthroponotic VL results from L. donovani (sensu stricto) transmission from human to insect vector to human. However, although L. donovani is generally considered a viscerotropic parasite, it has also been sporadically implicated in cases of cutaneous leishmaniasis in India and Sri Lanka (Karunaweera et al, 2003;Nawaratna et al, 2009;Sharma et al, 2009). Recently, in Sri Lanka, increasing numbers of cutaneous leishmaniasis caused by L. donovani infection have been reported and there is limited evidence suggesting that it may be a zoonotic form of the disease (Nawaratna et al, 2009).…”
mentioning
confidence: 99%